Gathering noise from my life : a camouflaged memoir - Anderson, Donald, 1946 July 9- (University of Iowa Press, 2012)
The noise gathered from a lifetime of engaging with war, race, religion, memory, illness, and family echoes through the vignettes, quotations, graffiti, and poetry that Donald Anderson musters here, fragments of the humor and horror of life, the absurdities that mock reason and the despair that yields laughter. Gathering Noise from My Life offers sonic shards of a tune at once jaunty and pessimistic, hopeful and hopeless, and a model for how we can make sense of the scraps of our lives. "We are where we've been and what we've read," the author says, and gives us his youth in Montana, the fami.